Using Quizziz Application to Make Online Evaluations during Covid-19 Pandemic: Teacher Competency Training - Setiyani Setiyani; Sri Sumarwati; Apri Dwi Astuti; Dina Pratiwi Dwi Santi; Try Suprayo (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
Various problems are faced by teachers, students, and parents when studying online during the Covid-19 pandemic. The teachers feel the overload upon students studying at home and completing school assignments. There is a need for innovation in assigning tasks to be more fun instead of a burden. One such innovation is using Quizizz. This community service aims to improve teachers’ competence in making online evaluations through the Quizizz application. The method applied to carry out the service is lectures, questions and answers, and practice. Nineteen teachers of Sadagori 1 Elementary School in Cirebon City participated in the program. The result showed that the teachers’ ability to make online quizzes using Quizizz increased to 100%. Beginner teachers who have never used or known the Quizizz application before could easily create and publish quizzes in Google Classroom. The involvement of tutors in each group helped the teachers to practice making quizzes using Quizizz. The participants were very enthusiastic about participating in the training. Hopefully, the training will be continued in the future.